Ancient marbles in Naples in the eighteenth century : findings, collections, dispersals - Dodero, Eloisa (Studies in the history of collecting & art markets ;, 2019)
"In Ancient Marbles in Naples in the Eighteenth Century Eloisa Dodero aims at documenting the history of numerous private collections formed in Naples during the 18th century, with particular concern for the "Neapolitan marbles" and the circumstances of their dispersal. Research has thus made it possible to formulate a synthesis of the collecting dynamics of Naples in the 18th century, to define the interest of the great European collectors, especially British, in the antiquities of the city and its territory and to draw up a catalogue which for the first time brings together the nucleus of sculptures reported in the Neapolitan collections or coming from irregular excavations, most of which shared the destiny of dispersal, in some cases here traced in definitive fashion"--